NOD2-NLRP3 Axis and Asthma - Cai X (Journal of Asthma and Allergy, 2025)
Xulong Cai Department of Pediatrics, Affiliated Hospital 6 of Nantong University, Yancheng Third People’s Hospital, Yancheng, 224000, People’s Republic of ChinaCorrespondence: Xulong Cai, Email caixulong2017@163.comAbstract: Patients with asthma frequently experience recurrent symptoms including coughing, wheezing, shortness of breath, and chest tightness. Asthma is a common public health concern. It is characterized by chronic airway inflammation. However, The pathogenesis of asthma is complex. Inflammasomes are signaling platforms that regulate the inflammatory response. There is a correlation between inflammasomes and asthma. Pattern recognition receptors recognize danger signals and participate in inflammasome activation. Nucleotide-binding and oligomerization domain-containing 2 (NOD2), a pattern recognition receptor, senses microbial components and triggers immune responses. There have been studies showing a correlation between NOD2 and asthma. The nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) participates in the formation of inflammasomes. NLRP3 are involved in asthma pathogenesis. In this review, we discuss the roles of NOD2 and NLRP3 in the pathogenesis of asthma.Keywords: NOD2, NLRP3, inflammasome, asthma